The effect of long-term cultivation without replanting on the viability of grape plants in vitro - Pavlova I.A.; Klimenko V.P.; Lushchay E.A.; Abdurashitova A.S.; Grigorenko M.I. (BIO Web of Conferences)
The vegetative collection of grape plants in vitro was previously created in the Institute Magarach. According to the method developed by scientists the Institute, the plants are maintained in a state of deep dormancy without lighting at a low temperature. A significant part of samples of the vegetative collection are Crimean autochthonous varieties – 41 %. The goal of research was to determine the viability of autochthonous varieties after long-term conservation without replanting, according to the developed method in a state of deep dormancy at a low positive temperature in the dark. Plants of 36 Crimean autochthonous varieties in vitro from the vegetative collection were used for the study. Biotechnological methods developed in the Institute Magarach were applied in the course of the experiments. Plants of 36 Crimean autochthonous varieties in vitro from the vegetative collection were used for the study. Biotechnological methods developed in the Institute Magarach were applied in the course of the experiments. The studies showed that 47.2% of Crimean autochthonous varieties have retained the viability of plants after long-term cultivation in the dark at a low positive temperature. Lethality was caused by bacterial infection, vitrification, and depended on the morphological condition of a sample and genotype. Regeneration capacity of buds was detected in 13.88% of varieties. Regeneration from the lower bud when cultivated without replanting after the end of conservation period was observed in 13.88% of varieties. The proportion of varieties that retained morphological structure was 19.44%. Growth processes of these plants resumed in the light. Depending on the genotype, shoot growth was 22.39-82.61%. In total, the plants were in different states without replanting for 16 months.